Polypeptide-dependent protein kinase from bakers' yeast. - Yanagita, Y (1987)
The purification and properties of a protein serine kinase (PK-P) extracted with Triton X-100 from membranes of bakers' yeast are described. The enzyme is virtually inactive unless either a histone or a heat-stable polypeptide from yeast membranes and Mg2+ are added. Other divalent cations substitute for Mg2+ poorly or not at all; most of them, including Mn2+, inhibit when added in the presence of 5 mM Mg2+. The enzyme is unstable but can be stabilized by addition of 0.1% Triton X-100 and 20% glycerol. The final preparation shows, on silver-stained electrophoresis gels, two major bands (Mr 41,000 and 35,000). According to gel filtration the molecular weight of the active protein is about 75,000. Of the two subunits, only the smaller one appears to be autophosphorylated. In addition to casein, the enzyme phosphorylates several proteins including the H+-ATPase (Mr 100,000) in the yeast plasma membrane. In order to demonstrate the phosphorylation of the ATPase (up to 0.9 equivalents), exposure of the latter to an acid phosphatase was required. Other phosphorylated proteins include mRNA cap-binding protein from mammalian erythrocytes and yeast, a glucocorticoid receptor protein, and a preparation of the guanine nucleotide-binding proteins Gi and Go from brain. A partial purification of a natural activator from yeast plasma membranes is described.